(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This paper deals with the notion of δ p(Λ,p)-open sets. Some properties of δ p(Λ,p)-open sets and δ p(Λ,p)-closed sets are investigated. Moreover, several characterizations of δ p(Λ,p)-D_1 spaces and δ p(Λ,p)-R_0 spaces are established.